Using Channel Hopping to Increase 802.11 Resilience to Jamming Attacks - Navda, Vishnu; Bohra, Aniruddha; Ganguly, Samrat; Rubenstein, Dan (IEEE Infocom Minisymposium, 2007)
802.11a, b, and g standards were designed for deployment in cooperative environments, and hence do not include mechanisms to protect from jamming attacks. In this paper, we explore how to protect 802.11 networks from jamming attacks by having the legitimate transmission hop among channels to hide the transmission from the jammer. Using a combination of mathematical analysis and prototype experimentation in an 802.11a environment, we explore how much throughput can be maintained in comparison to the maintainable throughput in a cooperative, jam-free environment. Our experimental and analytical results show that in today’s conventional 802.11a networks, we can achieve up to 60% of the original throughput. Our mathematical analysis allows us to extrapolate the throughput that can be maintained when the constraint on the number of orthogonal channels used for both legitimate communication and for jamming is relaxed.